Analisis Hukum Terhadap Kedudukan Wali Nikah Bagi Seorang Janda Menurut Imam Abu Hanifah - Putra Diyansyah (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2022)
Marriage can be interpreted as an inner and outer bond between a man and a woman that is valid if the conditions and pillars are met, one of which is the role of a guardian in the marriage contract, which means that guardians in general are someone whose position is in authority over the names of others. Therefore, the problem that will be raised in this thesis is how the position of the guardian of marriage for a widow according to Imam Abu Hanifah, how is the legal istinbath method. This research is a library research (Library Research) which is a method of collecting data such as books related to the opinion of Imam Abu Hanifah written by other authors, because so far there has been no book written by him, while this research is descriptive analysis, namely by explaining, examine and analyze the opinions expressed by Imam Abu Hanifah. The results of this study indicate that the opinion expressed by Imam Abu Hanifah is that it is permissible for a widow to carry out a marriage contract by herself on the condition that the woman is mature, reasonable, a proper dowry, sekufu, and independent. This opinion is in accordance with the reasons used based on the strong arguments of the Qur'an and the hadith of the Prophet Muhammad.